Vocabularius incipiens teutonicum ante latinum. Konzeption und Geschichte eines deutsch-lateinischen Vokabulars des Spätmittelalters - Müller, Peter O. (Lexicographica, 2024)
The article is dedicated to the Vocabularius incipiens teutonicum ante latinum, an alphabetic vocabulary of the late Middle Ages with a German-Latin structure that served as an aid for acquiring knowledge of Latin. Its printing history extends from around 1481 to 1515. The article locates this vocabulary in the context of late medieval German-Latin lexicography, explains its conception and offers an overview of the printing history and revision strategies.
CRIS-Team Scopus Importer:2024-12-06
Keywords: alphabetic lexicography; German-Latin lexicography; humanistic lexicography; late medieval lexicography; macrostructure; microstructure; printing history; revision strategies